Sweating the metal flying under fire ; a Chinook pilot's blistering account of life, death and dust in Afghanistan - Duncan, Alex (Hodder & Stoughton, 2011)
The Chinook comes in to land in one of the most dangerous parts of Afghanistan. At the machine's controls is one man and if he doesn't stay calm, then everyone could die. That man is Flt Lt Alex 'Frenchie' Duncan and he's been involved in some of the most daring and dangerous missions undertaken by the Chinook force in Afghanistan. Here, he tells the action-packed true story of the Chinook helicopter force in Afghanistan